Partnership between a consumer-led mental health research network and a large mental health research organisation: an Australian mixed methods case study - Michelle Banfield; Bridget Berry; Grenville Rose; Tim Heffernan; Richard Schweizer; Bani Aadam; Katherine Gill; Bradley Foxlewin; Peter Schaecken; Angelica Trias (Research Involvement and Engagement)
Abstract Aim This paper presents a case study review of an Australian research partnership between an independent mental health lived experience-led research network and an academic organisation established for the research and treatment of disorders of the brain and mind. The aim of the study was to explore the principles and practical requirements needed for a successful partnership that promotes inclusive research practices and power sharing and provide a framework to improve the operationalization of future similar partnerships. Methods This study was led and conducted by lived experience researchers. We used a mixed-method approach to data collection for data triangulation. An environmental scan of peer-reviewed and grey literature on mental health research partnerships was conducted, followed by a three-part data collection with members of both organisations. Data collection comprised an online survey, in-depth interviews, and a roundtable discussion to integrate findings and formulate recommendations. Results and Conclusion This case study explores and describes a missed opportunity of a consumer led mental health research organisation to work successfully with an established mental health research organisation. Poor communication and unclear processes led to unmet expectations on both sides. Findings suggest the use of reflective practice by team members of both partner organisations may have been helpful in identifying further improvements to inclusive research practice, empowering consumers in inclusive mental health research.